Communication Protocols in Public Health: A Case Study of Vector-borne Diseases. (June 2017) - Dwivedi, Siddharth; Sagar, Mahim
This work was initiated primarily to analyze the role of communication in public health policy and hence develop protocols to design effective communication strategies. Research was motivated by the fact that the traditional approaches towards communication in health management have proved inadequate in front of the complexity of recent challenges. New and innovative 'Integrated Communication Strategies', which employ targeted communication tools for achieving public cooperation, have emerged as the need of the hour. This was revealed by the extensive literature review carried out by the authors. The fact that most of the researches so far have been either to empirically determine factor linkages and hierarchies on a small population sample or to analyze some specific aspect of the whole public communication architecture restricts their usability to large-scale, real-life situations. This research aims at constructing that big picture, a wholesome view of the role communication is expected to play in a public health programme and how the researches so far can be collated with insights from the case study of dengue fever in New Delhi carried out by the authors to yield protocols for designing highly effective communication programmes, which shall go long way in ensuring a successful health campaign.